From soundscapes to societies: investigating gamelan's cultural impact through the socio-karawitanology paradigm - Sularso Sularso; Bao Hanshi; Qinyu Yu (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
This article investigates the auditory environment, known as "soundscapes," created by Gamelan, which comprises a distinctive combination of instruments, melodies, rhythms, and timbres that collectively shape the sonic experience. Recognizing the significance of understanding the auditory dimension of Gamelan and its influence on Indonesian society's cultural and social fabric, we explore the socio-karawitanology paradigm as the primary research topic. Our objective is to establish a novel gamelan research paradigm by integrating insights from sociology and karawitanology. The research methodology incorporates data from international journal articles and proceedings while also incorporating additional sources like field observations, expert interviews, and active engagement with the local community to ensure a comprehensive understanding of karawitan and its socio-cultural significance. Our analysis reveals that the socio-karawitanology paradigm provides a valuable framework for exploring the intricate and dynamic social dimensions prevalent in contemporary societal issues. The research contributes significantly by introducing the socio-karawitanology paradigm, opening avenues for fresh perspectives and insights in the field of karawitanology. It fosters a broader understanding of the socio-cultural impact of karawitan and stimulates further investigations into the interplay between music, society, and culture.